Kontekstualisasi Metode Tarbiyatul Aulad Abdullah Nashih Ulwan bagi Anak Disabilitas dalam Perspektif Pola Asuh Baumrind - Azmi Izuddin; Farahana Zahro Aini; Ali Mas’ud (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines the educational framework proposed by Abdullah Nashih Ulwan in Tarbiyatul Aulad fil Islam and its applicability to children with disabilities, analyzed through the lens of Diana Baumrind's parenting style theory. Employing a qualitative descriptive methodology with a library research design, this study draws on primary sources from the foundational works of both scholars. Data were analyzed through content analysis using comparative and syncretic techniques to identify convergence between classical Islamic educational values and contemporary developmental psychology. The findings reveal that Ulwan's five educational methods are: modeling (al-qudwah), habituation (al-'adah), admonition (al-mau'idzah), attentiveness (al-mulahazah), and disciplinary consequence (al-'uqubah). Exhibit a strong structural correspondence with Baumrind's authoritative parenting typology, which is characterized by the integration of high demandingness and high responsiveness. This synthesis yields a disability-inclusive model of Islamic Religious Education, wherein the independence and spiritual resilience of students with special needs are cultivated through a disciplinary framework that is simultaneously Sharia-grounded, democratic, and empathetic. The resulting paradigm, termed Authoritative-Religious, provides a theoretical foundation demonstrating that classical Islamic educational values retain their relevance and efficacy in addressing the pedagogical challenges of contemporary inclusive education.   Keywords: Abdullah Nashih Ulwan, Diana Baumrind, Disability Education, Inclusive Islamic Education